ApoE isoform- and microbiota-dependent progression of neurodegeneration in a mouse model of tauopathy - Seo, Dong-Oh; O'Donnell, David; Jain, Nimansha; Ulrich, Jason D; Herz, Jasmin; Li, Yuhao; Lemieux, Mackenzie; Cheng, Jiye; Hu, Hao; Serrano, Javier R; Bao, Xin; Franke, Emily; et al. (Science (American Association for the Advancement of Science), 2023)
Tau-mediated neurodegeneration is a hallmark of Alzheimer's disease. Primary tauopathies are characterized by pathological tau accumulation and neuronal and synaptic loss. Apolipoprotein E (ApoE)-mediated neuroinflammation is involved in the progression of tau-mediated neurodegeneration, and emerging evidence suggests that the gut microbiota regulates neuroinflammation in an APOE genotype-dependent manner. However, evidence of a causal link between the microbiota and tau-mediated neurodegeneration is lacking. In this study, we characterized a genetically engineered mouse model of tauopathy expressing human ApoE isoforms reared under germ-free conditions or after perturbation of their gut microbiota with antibiotics. Both of these manipulations reduced gliosis, tau pathology, and neurodegeneration in a sex- and ApoE isoform-dependent manner. The findings reveal mechanistic and translationally relevant interrelationships between the microbiota, neuroinflammation, and tau-mediated neurodegeneration.